Interaction quality or time quantity? A systematic literature review on the role of working parents in early childhood vocabulary outcomes - Puspitasari, Th Atta Sekar; Syamsudin, Amir; Maryatun, Ika Budi (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2025)
Background: Early childhood language development is strongly influenced by the quality of verbal interaction within the family environment. This includes families in which parents are working and daily communication patterns may shift due to time constraints. Variations in interaction quality such as responsiveness, turn-taking, and exposure to vocabulary are understood to play a significant role in children’s vocabulary growth. Objective: This study aims to analyze the role of working parents in the vocabulary development of early childhood and to identify communication strategies used in conditions of limited shared time. Method: This study employed a systematic literature review approach. Articles published between 2015 and 2024 were collected from the Scopus, Web of Science, Google Scholar, and DOAJ databases. A structured screening process was conducted based on predefined inclusion and exclusion criteria, resulting in 42 eligible articles that were reviewed and synthesized thematically. Results: The analysis shows that most studies report a positive association between the quality of parent–child verbal interaction particularly responsiveness, conversational turn-taking, and lexical richness and children’s vocabulary growth. More than half of the reviewed articles also identified effective communication strategies, including dialogic reading, open-ended questioning, and consistent labeling of objects and actions. These strategies were found to remain effective even when parental time with children was limited. Conclusion: The findings indicate that language stimulation can still occur optimally through brief yet intentional interactions, even among working parents. This review provides a comprehensive understanding of communication patterns in working families and highlights important directions for future research in early childhood language development.